The Role of the Community in Developing Ecotourism Potential in Kiluan Village, Kelumbayan District, Tanggamus Regency - Dewi Ayu Hidayati , Dewi Ayu Hidayati; marvenda, Laras (Journal of Tourism and Creativity, 2025)
This study aims to determine the role of the local community of Pekon Kiluan Negeri in developing ecotourism potential and the factors that support and inhibit ecotourism development. This type of research is descriptive qualitative research. The number of informants in this study was 10 people determined through purposive sampling. The data collection techniques used were in-depth interviews, observation, and documentation. The results of this study indicate that the community in Pekon Kiluan Negeri participated in the planning, implementation, and monitoring of ecotourism activities. However, after COVID-19, community concern and involvement have begun to decrease, because Kiluan tourism has fluctuated so that the community no longer benefits from ecotourism, only a few are still involved so the role of the community is not as optimal as before.